PENGARUH TERAPI MUSIK TERHADAP PENURUNAN TINGKAT KECEMASAN PADA ANAK YANG DIRAWAT DI RUMAH SAKIT Dr.OEN SURAKARTA - Rahayu Setyaningsih; Sri Aminingsih; Linda Yuni Hastari (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2014)
AbstractBackground. Hospitalization is a process that for some reason or emergency plans, so the children had to be hospitalized can cause children to experience anxiety. To overcome anxiety management can be given psychotherapy, one of which is with music therapy. Based on the data obtained through patient registration book entry of data obtained that the number of pediatric patients aged 3-6 years who were admitted to Teratai Ward. Dr. Oen Surakarta in September amounted to 43 children, with the number 5 top disease was observed febrile illness (14 children), abdominal pain (5 children), vomiting (5 children), DHF (5 children) and bronchopneumonia (4 children). The research objective of this study was to determine the effect of music therapy to decrease the level of anxiety in children who were treated at the Dr. Oen Surakarta Hospital before and after the given music therapy. Research method The research used in this study is the approach Quasy Experiment with one group pre-test and post-test. Using purposive sampling with a sample size of 30 children. Collecting data using the observation sheet in the form of a checklist. Results: The results of the analysis using dependent test paired samples T-test SPSS version 18.0 with Î± = 5% (0.05), obtained results show 21 312 t with p value of 0:00. so p value of <0.05., which means that there is an influence of music therapy to decrease the level of anxiety in children who were treated at the Hospital Dr. Oen Surakarta. Conclusion: There is a decrease in the effect of music therapy on anxiety levels in children who were treated at the Dr. Oen Surakarta Hospital.Keywords : Music Therapy, Anxiety, Hospitalization.